Recycling of Chromite Waste for Concrete: Full Factorial Design Approach - Mesci, B.; Elevli, S. (Springer International Publishing AG, 2012)
Recently full factorial design approach has been used to assess the recycling potential of a given waste. The objective of this study is to identify the significant factors and interactions involved in maximizing compressive strength of concrete when chromium waste is used as admixture. In this respect, experimental factors at two levels, which are admixture type (chromite/ chromite+ superplastizer), admixture percentage (5- 15%) and cure duration (7-28 days), are selected as possible candidates affecting the compressive strength. The modeling technique presented in this paper is based on 2 3 full factor experimental design and can easily be implemented to see the effect of any input factor on a given response variable. According to the full factorial analysis, at the 5% percentage level when Naphtalene sulfonate is added to concrete with chromite waste, the compressive strength will be good enough after 28 days. The results demonstrate that chromite waste after neutralization can be used in construction industry.
Keywords: ANOVA; Chromite Waste; Experimental Design